Characterization of Thermostable α–Amylase from Germinating Cowitch (𝙈𝙪𝙘𝙪𝙣𝙖 𝙥𝙧𝙪𝙧𝙞𝙚𝙣𝙨 (L.) DC.) Seeds - Thummavongsa, Theera; Posoongnoen , Saijai; Wongsooksin , Kamonchanok; Jandaruang , Jinda; Prajanban , Bung–on; Preecharram, Sutthidech (Burapha Science Journal, 2026)
Purification of α–amylase from germinating cowitch (Mucuna pruriens (L.) DC.) seeds (MpAmy) was carried out using two steps of 35 – 65% (w/v) Ammonium sulphate fractionation and β–cyclodextrin sepharose 6B affinity chromatography. The enzyme was purified 216.4–fold with a final specific activity of 91.0 U/mg. Sodium Dodecyl Sulfate Polyacrylamide Gel Electrophoresis (SDS – PAGE) analysis exhibited a molecular weight of MpAmy at 58 kDa which corresponded with amylase activity by Zymographic method. Characterization of MpAmy showed high activity at the pH of 5.0 – 6.0 and the high temperature of 50.0 – 90.0 ºC. The optimum pH and temperature for the enzyme were at pH 5.0 and 60.0 ºC, respectively. Furthermore, MpAmy was found stable at a wide range of pH 5.0 to 7.0, pH and the temperature between 30 ºC to 90 ºC. The Michalis constant (Km) and Maximum velocity (Vmax) for hydrolysis of starch were 2.1 mg/mL and 0.2 µmoles/min/mL, respectively. The MpAmy showed the highest specific activity toward starch followed by amylopectin and glycogen as their natural substrates. The enzyme catalyzed Ethylidene–pNP–G7 at 280.8 nmol/min/mL, indicating it was an alpha amylase. The results from enzyme characterization indicated that MpAmy is the Thermostable α–amylase. Therefore, MpAmy has the potential for applying in different industries, especially the starch industry.